Vocational High School Community Service As Innovative Community Empowerment Program : A Case Study of Garut Vocational High School - Ipan Ilmansyah Hidayat; Sri Nurhayati; Gumpanat Boriboon (Universitas Pendidikan Mandalika, 2024)
This research aims to describe vocational service programs, especially at SMKN 1 Garut, as innovative community empowerment. This study used a case study method with a qualitative approach. This case study was conducted through interviews with five informants, non-participant observation, and document study. The collected data were analyzed using inductive analysis. The results showed that the vocational high school community service programs serve as innovative community empowerment programs. This case study found that the participation of vocational schools (SMK) in community service activities catalyzes the fostering of more robust connections between educational institutions and their local communities. Forms of SMK participation in community service activities cover ten expertise skills which serve as the foundation for the school's community empowerment initiatives, where community members are engaged and empowered through various programs and activities. The alignment of expertise competencies with community needs is crucial to ensure the relevance and effectiveness of the programs. Some programs, such as Logistics Management and Renewable Energy Engineering, have encountered resistance due to perceived irrelevance to community skill development. The research recommends a comprehensive evaluation of the specific needs within the local area for an effective and well-developed implementation of the community program.